A educação ambiental na escola básica: diretrizes para a divulgação dos conhecimentos científicos - Reis, Marília Freitas de Campos Tozoni [UNESP]; Talamoni, Jandira Liria Biscalquini [UNESP]; Ruiz, Sonia Silveira [UNESP]; Neves, Juliana Pereira [UNESP]; Teixeira, Lucas André [UNESP]; Cassini, Luciana Falcon [UNESP]; Festozo, Marina Battistetti [UNESP]; Janke, Nadja [UNESP]; Maia, Jorge Sobral da Silva [UNESP]; Santos, Helena Maria da Silva [UNESP]; Cruz, Lilian Giacomini [UNESP]; Munhoz, Regina Helena [UNESP] (My University, 2012)
The study from which this paper is drawn aimed to identify and understand elementary education teachers’ sources of information on environmental education (EE) to contribute to inserting EE into elementary school. The study was based on a qualitative approach and was conducted using field research. Data were collected by observations and interviews with about three-hundred teachers in fourteen cities in the central region of the state of São Paulo. Here we present the conclusions of the study: the systematization of publication guidelines which could help the insertion of environmental education into elementary education. In that regard, we indicate the need to question such guidelines along with the scientific community, as well as to create, in initial and continuing teacher training, spaces to debate more appropriate ways of searching for information on environmental education.

El estudio que originó este artículo tuvo como objetivo comprender las fuentes de información de los(las) profesores(as) de la educación básica sobre educación ambiental (EA) para contribuir para la inserción de esta en la escuela básica. Fue un estudio cualitativo en la modalidad investigación de campo y los datos para análisis se colectaron por observaciones y entrevistas con cerca de trescientos profesores y profesoras en catorce municipios de la región central del estado de São Paulo. Presentamos aquí las conclusiones finales del estudio: la sistematización de directrices para publicaciones más adecuadas para la inserción de la EA en la educación básica. Apuntamos, en este sentido, la necesidad de problematizar con la comunidad científica esas directrices, como también de crear, en la formación inicial y permanente de los(las) profesores(as), espacios de discusión de formas adecuadas de búsqueda de informaciones sobre educación ambiental.

O estudo que originou este artigo teve como objetivo compreender as fontes de informação dos(as) professores(as) da educação básica sobre educação ambiental (EA) para contribuir para a inserção desta na escola básica. Foi um estudo qualitativo na modalidade pesquisa de campo e os dados para análise foram coletados por observações e entrevistas com cerca de trezentos professores e professoras em catorze municípios da região central do estado de São Paulo. Apresentamos aqui as conclusões finais do estudo: a sistematização de diretrizes para publicações mais adequadas para a inserção da EA na educação básica. Apontamos, nesse sentido, a necessidade de problematizar com a comunidade científica essas diretrizes, como também de criar, na formação inicial e permanente dos(as) professores(as), espaços de discussão de formas adequadas de busca de informações sobre educação ambiental.
Environmental education in elementary school: guidelines for scientific knowledge dissemination
La educación ambiental en la escuela básica: directrices para la divulgación de los conocimientos científicos
Keywords: Teacher training; Information sources; Knowledge dissemination; Formación de educadores; Fuentes de información; Divulgación de conocimientos; Formação de educadores; Fontes de informação; Divulgação de conhecimentos